The Influence of Religiosity on Prosocial Behavior in Adolescents in Makassar City - Yusuf, Jannatul Ma’wa; Razak, Ahmad (Polteknik Ilmu Pemasyarakatan, 2023)
Prosocial behavior is a helping behavior without expecting any reward from the individual being helped. This study aimed to determine the influence of religiosity on prosocial behavior in adolescents in the city of Makassar. The study used a quantitative descriptive approach method. The respondents in this study were 300 teenagers from Makassar city. In this study sample selection used the technique of accidental sampling. The measuring instruments used in this study used the modified Glock and Stark religiosity scale from the Astuti scale (2022) and the modified Mussen prosocial scale from the Salamah (2021) scale. Data analysis uses a simple linear regression technique. The results showed that there was a positive influence of religiosity of 13.6% with a significance value of 0.000 < 0.05 which means that there is an influence of religiosity on prosocial behavior in adolescents in Makassar city. The results of the analysis showed that the value of p = 0.000 < 0.05 indicates that there is a significant influence between religiosity and prosocial behavior in adolescents in the city of Makassar. At the R-Square value there is a result of 0.136%, so it can be concluded that religiosity affects prosociality by 0.136%. Correlation value of person r = 0.135% indicates that there is a positive influence between religiosity and prosocial behavior in adolescents in Makassar city.